IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH PADA DINAS LINGKUNGAN HIDUP KOTA PALU - Siti, Hardiana; Susanti, Ani; Hamid, Abdul (JPS: Journal of Publicness Studies, 2024)
This study aims to determine the implementation of waste management policies at the Environmental Service of Palu City. The research method used is descriptive qualitative, which provides an overview of the phenomena or factors of the problem under study according to existing facts. Data collection techniques are observation, in-depth informant interviews and documentation to collect data. Informants in this study amounted to 7 people. The theory used is George C. Edward III where there are four indicators, namely communication, resources, disposition and bureaucratic structure. Based on the results of the study, it can be concluded that the implementation of waste management policies at the Environmental Service of Palu City, in general, the implementation of waste management is quite good. This can be seen from the indicators of the research results, which include aspects of communication to some people that are still lacking, in the transmission indicator it can be seen that policy dissemination has been carried out by the government, but the delivery of information and clarity regarding waste management is still not effective. Human resources are still lacking, the budget for operational funds related to sub-activities or waste programs is insufficient, as well as facilities to support the success of policy implementation such as TPS, TPS 3R, and an inadequate waste transportation fleet, Disposis or the attitude of implementers is good because policy implementers have carried out their duties and good standard operating procedures (SOP) for waste management. As for suggestions so that the implementation of waste management policies at the Palu City Environmental Service runs well, the Environmental Service must improve communication, namely in the transmission or dissemination of information evenly to the community. improve the quality of human resources by providing special training related to waste management to staff so that they are able to perform their duties more optimally and need to increase facilities and infrastructure such as waste transportation fleets and the availability of TPS, TPS 3R. And for the community it is recommended that there is a need for awareness to care about waste management in Palu City.